Optimizing Educational Leadership: Building Sustainable Education in the 5.0 Era - Tursina, Nani (Letiges, 2023)
Leadership is a sensitive issue because it involves whether or not an educational institution is being led. Leaders have the power to move and influence the tasks that their duties and responsibilities must carry out. This study aims to describe school principals as leaders of educational institutions in the 5.0 era, internalize the EMASLIM-FM concept for the function of educational leadership in the 5.0 era and describe school principals as visionary education leaders in the 5.0 era. This research is a qualitative type, using a library research approach. Data were obtained through literature studies of books, ebooks, scientific journal articles, dissertations and other sources that pay attention to their relevance. Data analysis using comparative analysis. The analysis results show that in the EMASLIM-FM concept, the school principal has the functions of educator, manager, administrator, supervisor, leader, innovator and motivator, figure and mediator. Leadership in the 5.0 era requires school principals to internalize visionary competencies for institutions so that they become plenary educational institutions. Creative leadership is essential and must be realized, considering that vision is a guideline in the wheels of leadership. The principal needs to implement the idea tangible and measurable in the leadership wheel. Concrete action in implementing the vision is the key to achieving the desired educational goals.